VARIASI GEN MITOKONDRIA CYTOCHROME B PADA DUA JENIS BURUNG KAKATUA PUTIH (CACATUA ALBA DAN C. MOLUCCENSIS) - Astuti, Dwi (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTVariation in The Mitochondrial Cytochrome b Gene in The Two White Cockatoo Species (Cacatua alba and C. molucensis). DNA sequence variation in the 791-bp of mitochondrial cytocrome b gene in the two white cockatoo species (C. alba and C. moluccensis) were analyzed in this study. Two pairs of internal primers used to amplify two fragments of cytochrome b from 30 individuals cockatoo. The results show that there were genetic variations among individuals of C. alba and C. moluccensis. Twenthy eight haplotypes occured in 30 individuals studied; 14 haplotypes (Hca1-Hca14) in 16 individuals of C. alba, and 14 haplotypes (Hcm1-Hcm14)in 14 individuals of C. moluccensis. Hca5 was dominant and owned by 3individuals (H37, KBS62, 28, BBP88). Within C. alba there were 18 variable sites, 0.00701 of nucleotide diversity (Pi), 0.975 ± 0.035 of haplotype diversity (Hd), and 0.005 ± 0.002 of mean genetic distance. Whitin C. moluccensis there were 18 variable sites, 0.00830 of Pi, and 0.9999± 0.028 of Hd, and 0,010 ± 0.002 (0.001-0.010) mean genetic distance. Divergence between C. alba and C. moluccensis was 0.064 ± 0.088 %. Neigbor-joining (NJ) analysis showed two main clusters consisted of : C. alba and C. moluccensis separately, and indicated that althoughthere were some variations in the DNA sequences, but the individuals within a species remain clustered in the same cluster.Key words: genetic variation, mitochndrial cytochrome b, cockatoo bird, Cacatua alba, Cacatuamoluccensis